The Post-Buckling State of a Multilayered Shell in a Form of a Cylinder Sector Subjected to an Unidirectional Compression and Simultaneous Shear - W. Walczak; N.X. Luu (Engineering Transactions)
In the paper are presented the results of theoretical analysis of post-buckling state of a thinwalled, elastic, multilayered shell in a form of a cylindrical sector, subjected to the action of unidirectional compression and simultaneous shear. The shell consists of orthotropic layers and has a symmetric structure. The problem is solved approximately on the basis of the non-linear version of the anisotropic shell theory given by S. A. Ambarcumian, The detailed numerical computations are made for a shell consisting of five orthotropic layers, and results of these computations are presented in the form of diagrams. The numerical computations were made on the ODRA-1204 computer.